2023
DOI: 10.5713/ab.22.0121
|View full text |Cite
|
Sign up to set email alerts
|

Screening of key miRNAs related with the differentiation of subcutaneous adipocytes and the validation of miR-133a-3p functional significance in goats

Abstract: Screening of key miRNAs related with the differentiation of subcutaneous adipocytes and the validation of miR-133a-3p functional significance in goats ABSTRACTObjective: Adipocyte differentiation is regulated by a variety of functional genes and non-coding RNAs. However, the role of miRNAs in lipid deposition of goat white adipose tissue is still unclear.Therefore, this study revealed the miRNA expression profile in goat subcutaneous adipocytes by sRNA-seq. Methods:The miRNA expressed in goat subcutaneous prea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…This study reveals that legume protein can influence lipid metabolism in ram lambs cells. Previous researchers (Li et al 2022;Zsolnai et al 2022) in pigs have shown similar results to the current study; it has been reported that feeding high protein diets can reduce lipogenesis activity.…”
Section: Lipid Regulationsupporting
confidence: 90%
See 1 more Smart Citation
“…This study reveals that legume protein can influence lipid metabolism in ram lambs cells. Previous researchers (Li et al 2022;Zsolnai et al 2022) in pigs have shown similar results to the current study; it has been reported that feeding high protein diets can reduce lipogenesis activity.…”
Section: Lipid Regulationsupporting
confidence: 90%
“…Studies reported by Adriani and Mushawwir (2020), Mushawwir et al (2020), andSun et al (2022) show that increasing insulin will increase the absorption of glucose into the cytoplasm. An increase in glucose in the cytoplasm stimulates an increase in acetyl-CoA so that the activity of glucose-6-pyruvat dehydrogenase (G-6-PDH) decreases (Mushawwir et al 2020;Li et al 2022). Furthermore, a decrease in G-6-PDH causes a decrease in NADPH production (Sejian et al 2021;Rahmania et al 2022).…”
Section: Lipid Regulationmentioning
confidence: 99%
“…Considering that SIRT1 suppresses adipogenesis through inhibition of PPARγ activity [37] and activation of Wnt/βcatenin signaling in white adipose tissue [38], these data suggested that miR-133a positively regulated adipogenesis through modulation of Sirt1 in sheep SVF cells. Similarly, a recent report from Li et al suggests that miR-133a serves as a positive regulator of adipogenesis in goat subcutaneous preadipocytes [39]. To further elucidate whether GAA suppresses adipogenesis through regulation of miR-133a, sheep SVF cells treated with GAA were transfected with miR-133a mimics.…”
Section: Discussionmentioning
confidence: 96%